The Information Security Cultures of Journalism. Issue 8 (13th September 2020) - Crete-Nishihata, Masashi; Oliver, Joshua; Parsons, Christopher; Walker, Dawn; Tsui, Lokman; Deibert, Ronald
Abstract: This article is an exploratory study of the influence of beat and employment status on the information security culture of journalism (security-related values, mental models, and practices that are shared across the profession). The study is based on semi-structured interviews with 16 journalists based in Canada in staff or freelance positions working on investigative or non-investigative beats. We find that journalism has a multitude of security cultures that are influenced by beat and employment status. The perceived need for information security is tied to perceptions of sensitivity for a particular story or source. Beat affects how journalists perceive and experience information security threats. Investigative journalists are concerned with surveillance and legal threats from state actors including law enforcement and intelligence agencies. Non-investigative journalists are more concerned with surveillance, harassment, and legal actions from companies or individuals. Employment status influences the perceived ability of journalists to effectively implement information security. Based on these results we discuss how journalists and news organisations can develop effective security cultures and raise information security standards.